Steam sterilization effect on the accuracy of friction-style mechanical torque limiting devices - Seyed Jalil Sadr; Ali Fayyaz; Minoo Mahshid; Aboulfazl Saboury; Ghassem Ansari (Wolters Kluwer Medknow Publications, 2014)
Aim: This study was aimed to evaluate the effect of steam sterilization on the accuracy (within 10%) of friction-style mechanical torque limiting devices (F-S MTLDs) to achieve their target torque values. Materials and Methods: Fifteen new F-S MTLDs were selected from Astra Tech (25 Ncm, Hader SA, La Chaux-de-Fonds, Switzerland), BioHorizons (30 Ncm, Dynatorq ITL, Irvine, California, USA), Dr. Idhe (15-60 Ncm, Dr. Idhe Dental, Eching/Munich, Germany). Every peak torque measurement was tested ten times before steam sterilization using Tohnichi torque gauge (6Tohnichi-BTG (-S), Japan). Steam sterilization was performed using a 100 cycle autoclave. Preparation steps were carried out for the devices before each autoclave sterilization cycle. Peak torque measurements were repeated after every sterilization cycle. Mean difference between the measured and the targeted torque values were evaluated before and after aging. Repeated-measures of ANOVA were used to compare the differences of accuracy between subjects. Bonferroni post-hoc test was used for pairwise comparison. Results: Autoclaving resulted in an increase in the error values (the difference between peak torque and target torque values) in all the three groups studied (P < 0.05), with only Astra Tech devices showing >10% (maximum 12%) difference from their torque values in 5% of the measurements. Conclusion: Steam sterilization effect differs between target torque and measured peak values with an increase trend. The peak torque values showed a significant decrease for BioHorizons, while a significant increase was noted for Astra Tech and no significant change in Dr. Idhe group after sterilization. Clinical Implication: Within the limitation of this study the torque output of each individual device deviated in varying degrees from target torque values. However, the majority of the new frictional-style devices tested in this study, delivered fairly consistent torque output within 10% of their preset target values after sterilization. Astra Tech devices were the only one showing more than 10% difference from their torque values in 5% of the measurements. Combined effects of sterilization and aging still needs to be determined.